Porous Microspheres of Casein/Amorphous Calcium Phosphate Nanocomposite: Room Temperature Synthesis and Application in Drug Delivery - Ding, Guan-Jun; Zhu, Ying-Jie; Cheng, Guo-Feng; Ruan, Yin-Jie; Qi, Chao; Lu, Bing-Qiang; Chen, Feng; Wu, Jin (Current Nanoscience, 2016)
Porous microspheres of casein/amorphous calcium phosphate nanocomposite are prepared using casein sodium salt, CaCl2, Na2HPO4•12H2O and Na2HPO4•12H2O in aqueous solution at room temperature. The effects of experimental parameters such as solution pH, casein sodium salt and ageing time on the product are investigated. Porous microspheres of casein/amorphous calcium phosphate nanocomposite are characterized by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, thermogravimetric (TG) analysis, and Brunauer-Emmett-Teller (BET) specific surface area and pore size distribution. The as-prepared porous microspheres of casein/amorphous calcium phosphate nanocomposite are favorable for drug loading and release using ibuprofen (IBU), docetaxel (Dtxl) and vitamin B5 (B5) as typical drugs, and show low cytotoxicity in the cytotoxicity test. Thus, porous microspheres of casein/amorphous calcium phosphate nanocomposite have promising applications in various biomedical fields such as drug delivery.
Keywords: nanostructures